Sustainable water engineering - Charlesworth, Susanne; Booth, Colin (Colin A.); Adeyeye, Kemi, 1979- (Elsevier, 2021)
Sustainable Water Engineering introduces the latest thinking from academic, stakeholder and practitioner perspectives who address challenges around flooding, water quality issues, water supply, environmental quality and the future for sustainable water engineering. In addition, the book addresses historical legacies, strategies at multiple scales, governance and policy.--Publisher's description.